Assessment of atmospheric air pollution in Himalaya through simultaneous determination of oxidation PAHs products using lichens as bioindicators - Rosero-Moreano, Milton; Andrés, Eduardo; Domeño, Celia; Nerín, Cristina (Jornada de Jóvenes Investigadores del I3A, 2014)
The method has implied the DSASE extraction with toluene as solvent; the SPE as clean-up step using NH2 cartridge and GC-MS ion trap system was used as detection method in chemical ionization mode. The final concentrations were around 7.694 to 0.833 μg g-1 for oxoPAHs and 1.627 to 0.332 μg g-1 for nitroPAHs